Cost-Effectiveness of Antihypertensive Therapy in Ischemic Stroke Patients - Rowiyah Sufi Nurul Janah; F.X. Sulistiyanto Wibowo S; Yustisia Dian Advistasari (VISIKES, 2026)
Ischemic stroke is an acute condition caused by the interruption of blood flow to the brain due to blood vessel obstruction, which can lead to permanent disability and death. Hypertension is a major risk factor and the most common comorbidity in ischemic stroke patients. The use of antihypertensive therapy in stroke patients plays a crucial role in controlling blood pressure and preventing complications, but it also increases the burden of medical costs. Therefore, a pharmacoeconomic evaluation is necessary to assess the cost-effectiveness of the therapy. This study aims to analyze patient characteristics and evaluate the cost-effectiveness of oral antihypertensive therapy in ischemic stroke patients at Hospital "X" from September 2024 to August 2025. The method used was Cost-Effectiveness Analysis (CEA) with the Average Cost-Effectiveness Ratio (ACER), in which the therapy with the lowest ACER is considered the most cost-effective. The results showed that the majority of patients were male (32 patients), and the largest age group was elderly aged 56–65 years (23 patients), with an average length of stay of 4.63 days. As a single therapy, calcium channel blockers (CCBs) demonstrated the lowest ACER value of Rp34,013.77, making them the most cost-effective therapy. In combination therapy, the combination of CCBs and beta-blockers had the lowest ACER value (Rp29,766.44). These results indicate that selecting the right antihypertensive therapy can improve cost efficiency and support more rational healthcare delivery.